Psychiatry in prisons: a comprehensive handbook - Wilson, Simon (Forensic focus, 2010)
Introduction: The history of prison psychiatry / Simon Wilson & Ian Cumming -- The current structure of the prison service / John Podmore -- Delivering mental health services in prison / Janet Parrott -- Health screening in prisons / Don Grubin -- Mentally ill prisoners and mental health issues in prison / Ian Cumming & Simon Wilson -- Suicide, attempted suicide and self-injury in prison / David Crighton -- Managing substance misuse in prison / James Tighe -- The young offender / Julie Withecomb -- Women in prison / Richard Taylor & Jessica Yakeley -- Elderly prisoners / Seena Fazel & Preeti Chhabra -- People with intellectual disabilities in prison / Kiriakos Xenitidis, Maria Fotiadou, Glynis Murphy -- Black and minority ethnic prisoners / David Ndegwa & Dominic Johnson -- Sex offenders and vulnerable prisoners / Rebecca Milner -- Consent to treatment, the mental health act, and the mental capacity act / Simon Wilson & Raj Dhar -- Hunger strike and food refusal / Danny Sullivan & Crystal Romilly -- Psychiatric reports / Huw Stone -- The lifer system in england and wales / Natalie Pyszora -- Psychology in prisons / Graham Towl -- Prison therapeutic regimes / Mark Morris -- Death in custody / Andrew Forrester -- Prisons inspection / Tish Laing-Morton & Colin Allen -- International perspectives i : an overview of us correctional mental health / Charles Scott & Barbara McDermott -- International perspectives ii : delivery of mental health services in new zealand prisons : context and approaches / Ceri Evans & Phil Brinded -- Inside-outside : ethical dilemmas in prison psychiatry / Gwen Adshead -- Prison language as an organisational defence against anxiety / Gabrielle Brown & Julian Walker